Insight into the ERVK Integrase – Propensity for DNA Damage - Bray, Samantha; Turnbull, Matthew; Hebert, Sherry; Douville, Renée N. (Frontiers in Microbiology, 2016)
Retroviruses create permanently integrated proviruses that exist in the host genome. Retroviral genomes encode for functionally conserved gag, pro, pol and env regions, as well as integrase (IN), which is required for retroviral integration. IN mediates viral genome insertion through 3´ end processing of the viral DNA and the strand transfer reaction. This process requires the formation of a pre-integration complex, comprised of IN, viral DNA and cellular proteins. Viral insertion causes DNA damage, leading to the requirement of host DNA repair mechanisms. Therefore, a failure of DNA repair pathways may result in genomic instability and potentially cause host cell death. Considering the numerous human diseases associated with genomic instability, the endogenous retrovirus-K (ERVK) IN should be considered as a putative contributor to DNA damage in human cells. Future research and drug discovery should focus on ERVK IN activity and its role in human conditions, such as neurological disease and cancers.